ANALISIS KESESUAIAN JURNAL PERKULIAHAN DOSEN DENGAN SILABUS PEMBELAJARAN TBI - Nasution, Sahadir; Lubis, Rayendriani Fahmei; Harida, Eka Sustri (Institut Agama Islam Negeri Padangsidimpuan, 2017)
This research is done at Institute Islamic Studies (IAIN) Padangsidimpuan to know about lectures’ learning teaching journal, about English Department (TBI) syllabus, and about compatibility between lectures’ learning teaching journal and English Department (TBI) syllabus for scientific and skill subjects. It has been done through qualitative approach by descriptive method. The primary source of research is lectures’ learning teaching journal for scientific and skill subjects and the secondary source of research is the syllabus. Document and interview are used as the instrument of research. The result showed that there is one of lecture’s learning teaching journal that is not suitable with English Department (TBI) syllabus for scientific and skill subjects. It’s caused the lecture didn’t teach subject in which meant by Syllabus. It means that most of the lecturers have taught based on the learning and teaching syllabus given.